Keindahan Gaya Bahasa Al-Quran; Suatu Tinjauan Isti'arah Dalam Juzuk Kedua - Roslan Ab Rahman; Hashim Mat Zin; Md Nor Abdullah; Hasan Al-Banna Mohamed (Universiti Sains Islam Malaysia, 2024)
The use of appropriate style of language or Uslub, in an expression, as employed in the Quran verses, plays an important role in effective communication of the message. Isti’arah, as one of the various styles of language in the Quranic language, is the focus of this study. Isti’arah is part of the component of “Bayan” in Arabic Balaghah, and forms a branch of knowledge within the context of styles of language, that contributes to the status of the Quran as a miracle. Isti’arah is also viewed as a prominent comparative factor which is able to capture the hearts and minds of mankind. The objective of this research is to investigate the implied meanings of Quranic verses through Isti’arah/styles of language, besides revisiting viewpoints of previous Balaghah scholars for the benefits of the present generation. Through Isti’arah, related Majaz expressions, which normally require higher imaginative capacities and insights, would be able to be understood. This study analyzes nine verses in Chapter Two of the Quran. The findings revealed that Balaghah Isti’arah plays an important role in ensuring that the message of the Quran verses is meaningful and conveyed effectively. Thus the position of Isti’arah, in particular, and Balaghah Al-Quran in general, are part of I’jaz Al-Quran, which has been proven that no man can challenge. It is an important aspect to be known, not only by learners of the Arabic language and religious studies, but also by every Muslim.